Discriminação, preconceito e o assédio no ambiente de trabalho. - CAMPOS, Gabriel da Costa; FELICIANO, Liz Tilio; MATIAS, Mikhail Kalinin Lamansov (261, 2023)
Nosso trabalho de conclusão de curso aborda a problemática da discriminação, preconceito e assédio no ambiente de trabalho, destacando a negligência e prática dessas ações por superiores. Destaca-se a falta de efetividade das leis devido ao medo, falta de conhecimento dos direitos ou dificuldade em identificar os tipos de assédios, resultando em um ciclo repetitivo que muita das vezes resulta em impunidade. Há também a discussão do impacto da discriminação na motivação, produtividade e vida pessoal dos colaboradores, enfatizando a naturalização de comportamentos tóxicos e a dificuldade em perceber e denunciar, especialmente por questões financeiras. Os objetivos incluem apresentar e analisar discriminação, preconceito e tipos de assédio, explorando problemas e propondo soluções. Foi abordado também a necessidade de conscientização e medidas preventivas para reduzir a ocorrência desses problemas no ambiente de trabalho. Palavras chave: Discriminação; Preconceito; Assédio no trabalho; Negligência; Eficácia das leis; Ciclo repetitivo; Impacto psicossocial; Comportamentos tóxicos; Conscientização; Medidas preventivas.

ABSTRACT This thesis explores the challenges of discrimination, prejudice, and harassment in the workplace, highlighting the negligence and, at times, active engagement in such behaviors by superiors. Emphasizing the repetitive nature of these situations, often going unpunished, the study underscores the inefficacy of laws due to fear, lack of awareness of rights, or difficulty in identifying various forms of harassment. The discussion delves into the impact of workplace discrimination on employee motivation, productivity, and personal life, with a focus on the normalization of toxic behaviors and the challenges in recognizing and reporting these incidents, particularly due to financial concerns. The overarching goals of this thesis involve presenting and analyzing workplace discrimination, prejudice, and various forms of harassment, exploring the resulting issues, and proposing solutions to mitigate these challenges. The work also addresses the need for awareness and preventive measures among employees to reduce the occurrence of discrimination, physical and psychological harassment, and other common workplace problems. Keywords: Discrimination, Prejudice, Workplace harassment, Negligence, Efficacy of laws, Repetitive cycle, Psychosocial impact, Toxic behaviors, Awareness, Preventive measures.
Keywords: Discriminação; Preconceito; Gestão e Negócios